Field tests of a timber queen-post truss and numerical analysis - Branco, Jorge M. (2008)
In-situ cyclic tests on an existing traditional timber truss were performed. The main goal of the tests was to evaluate the overall behavior of the timber truss under symmetric and non-symmetric loading. Moreover, the influence of the location of point loads application, without and with eccentricity relatively to joints, was assessed. The carrying tests were preceded by a visual and non-destructive inspection aiming to collect geometric data and to assess the decay level. The field tests results of a queen-post truss are presented and analyzed. A numerical model was developed to reproduce the test results.